1997
DOI: 10.1021/jp962332p
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Specific Kinetics of Hydroxyl Radical (OH) with Water (H2O):  Testing Models of Reactivity and Atmospheric Fractionation

Abstract: Gas-phase hydrogen (H) abstractions from molecules by free radicals have been studied extensively. They form the simplest class of elementary reactions and also play a key role in atmospheric chemistry and so are the centerpiece of models of reactivity. Despite intense scrutiny, two fundamental mechanistic issues remain unresolved:  (1) Do H abstractions proceed directly or indirectly? (2) Do thermodynamic or electronic interactions determine their reaction barrier? The thermoneutral identity reaction, OH + H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
135
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 35 publications
22
135
1
2
Order By: Relevance
“…In this regard, the situation encountered here is similar to the OH isotopic budget of the stratosphere : indeed, the dryness and the low temperature prevailing in the stratosphere have led modelers to predict significant isotope anomalies in the stratosphere up to 40 ‰ according to Lyons (2001), above 30 ‰ for Zahn et al (2006). Due to the increase of temperature and the concomitant increase of the water vapor content and to the high temperature dependency of the isotopic equilibrium (Dubey et al, 1997), the x factor exhibits a marked decrease over the course of the measurement campaign, from values around 70 % at the beginning of the measurement campaign to values lower than 20 % at the end of the campaign. Therefore, if OH was produced with a significant isotope anomaly, this anomaly would be present at the beginning of the measurement campaign but would have largely disappeared toward the end of the campaign.…”
Section: O(oh)supporting
confidence: 52%
See 2 more Smart Citations
“…In this regard, the situation encountered here is similar to the OH isotopic budget of the stratosphere : indeed, the dryness and the low temperature prevailing in the stratosphere have led modelers to predict significant isotope anomalies in the stratosphere up to 40 ‰ according to Lyons (2001), above 30 ‰ for Zahn et al (2006). Due to the increase of temperature and the concomitant increase of the water vapor content and to the high temperature dependency of the isotopic equilibrium (Dubey et al, 1997), the x factor exhibits a marked decrease over the course of the measurement campaign, from values around 70 % at the beginning of the measurement campaign to values lower than 20 % at the end of the campaign. Therefore, if OH was produced with a significant isotope anomaly, this anomaly would be present at the beginning of the measurement campaign but would have largely disappeared toward the end of the campaign.…”
Section: O(oh)supporting
confidence: 52%
“…Therefore we cannot estimate the 17 O value of the produced OH. Dubey et al (1997) (Michalski et al, 2003). Given the fact that H 2 O represents an enormous non-anomalous oxygen reservoir in the atmosphere with respect to OH, such a reaction tends to erase the isotope anomaly of OH.…”
Section: O(oh)mentioning
confidence: 99%
See 1 more Smart Citation
“…SO 2 has 17 O = 0 ‰ due to the rapid isotopic exchange with abundant vapor water whose 17 O is near 0 ‰ (Holt et al, 1981). S(IV) oxidation by H 2 O 2 and O 3 leads to 17 O(SO 2− 4 ) = 0.7 and 6.5 ‰, respectively, on the basis of 17 O(H 2 O 2 ) = 1.4 ‰ (Savarino and Thiemens, 1999) and assuming 17 O(O 3 ) = 26 ‰ (Vicars and Savarino, 2014;Ishino et al, 2017 (Dubey et al, 1997;Luz and Barkan, 2005;Lee et al, 2002;Bao et al, 2000). Sulfate produced by NO 2 oxidation is suggested to occur either via a radical chain mechanism (Shen and Rochelle, 1998), via oxygen-atom transfer from OH − (Clifton et al, 1988), or from O 2 based on experimental results of He et al (2014) (Fu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies with isotope labeling of H atoms have shown that the above H atom transfer is extremely (Dubey et al, 1997). The theoretical calculated rate constant for the same reaction has been reported as 1.67 × 10 -16 cm 3 molecule -1 s -1 at 300 K (Uchimaru et al, 2003).…”
Section: Introductionmentioning
confidence: 89%